WHAT STRICTO SENSU GRADUATE PROGRAM TEACHERS UNDERSTAND BY THE REFLECTIVE TEACHER AND RESEARCHER TEACHER - Kreuzberg, Fernanda (2013)
The objective of this research was to analyze the understanding of graduate degree teachers regarding the reflective teacher and researcher teacher. Interviews of a descriptive and qualitative nature were conducted with 10 teachers from a graduate Accounting degree who taught in the last quarter of 2011. The majority respondents understand the researcher teacher as not only concerned with teaching, but also with research, in order for knowledge to evolve. The researcher teacher assumes the role of a mediator in addition to being a passer-on of knowledge. Reflective teachers were understood as those able to regulate their actions and present a systematic method of thinking, but not necessarily a critical thinking about teaching. It was observed that there is an approximation of the concepts of researcher and reflective teachers among the teachers surveyed, however of them focusing on their students attitudes, than in their own vision of teaching . The researcher teacher was also occasionally thought to be too merely focused on research that was not necessarily research on teaching, while reflective teachers were understood to sometimes lack an emphasis on the relationship between theory and practice in teaching.